“I Won't Shop Anywhere Else!”: Tokopedia Customer’s Love and Trust - Monica Pricilia Angelie; Honey Wahyuni Sugiharto Elgeka; Anton Johannes Tjahjoanggoro (Journal of Educational, Health and Community Psychology, 2023)
The number of customers constantly changes for each marketplace in Indonesia, including Tokopedia. This is determined by customers’ loyalty toward each marketplace. This study is aimed at identifying the relationship between love and trust with customer loyalty towards Tokopedia. A purposive sampling technique was applied and samples of 274 participants were retrieved. The study’s data was analyzed using multiple linear regression, which showed that love (decision/commitment and intimacy) had a positive relationship with customer loyalty, whereas trust had no significant association with customer loyalty. This indicates that customer loyalty can be established through interpersonal relationships between sellers and buyers in a marketplace, and that trust may not necessarily have a direct role in shaping customer loyalty without social attachment and interactive communication between sellers and buyers.